2015
DOI: 10.1007/s10484-015-9313-x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral, Cognitive, and Motor Preparation Deficits in a Visual Cued Spatial Attention Task in Autism Spectrum Disorder

Abstract: Abnormalities in motor skills have been regarded as part of the symptomatology characterizing autism spectrum disorder (ASD). It has been estimated that 80% of subjects with autism display “motor dyspraxia” or clumsiness that are not readily identified in a routine neurological examination. In this study we used behavioral measures, event-related potentials (ERP), and lateralized readiness potential (LRP) to study cognitive and motor preparation deficits contributing to the dyspraxia of autism. A modified Posn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 94 publications
2
15
0
1
Order By: Relevance
“…That is, in ADHD findings of combined neuropsychological and event‐related potential (ERP), paradigms consistently demonstrated atypical ERP components locked to alerting cues for upcoming targets (Cue‐P3; CNV) (Kratz et al, ; Ortega, López, Carrasco, Anllo‐Vento, & Aboitiz, ). In ASD, atypical reorienting has instead been associated with stimulus‐locked ERP components (Sokadhze et al, ). Indeed, across studies with cognitive‐neurophysiological paradigms, altered attentional processing in ADHD most consistently relates to alerting cues; and in ASD to the relative novelty of the stimulus following a cue (Lau‐Zhu, Fritz, & McLoughlin, ).…”
Section: Introductionmentioning
confidence: 99%
“…That is, in ADHD findings of combined neuropsychological and event‐related potential (ERP), paradigms consistently demonstrated atypical ERP components locked to alerting cues for upcoming targets (Cue‐P3; CNV) (Kratz et al, ; Ortega, López, Carrasco, Anllo‐Vento, & Aboitiz, ). In ASD, atypical reorienting has instead been associated with stimulus‐locked ERP components (Sokadhze et al, ). Indeed, across studies with cognitive‐neurophysiological paradigms, altered attentional processing in ADHD most consistently relates to alerting cues; and in ASD to the relative novelty of the stimulus following a cue (Lau‐Zhu, Fritz, & McLoughlin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Our study also explored whether these prospective biomarkers were shared or distinct in comorbid ASD+ADHD by using a behavioral screening (RT, error rate, post-Non error RT adjustment) and ERP paradigm (ERP at frontal and parietal sites, response-averaged errorrelated negativity, and error-related positivity) that we implemented in previous studies Sokhadze, El-Baz, Sears, Opris, & Casanova, 2014;Sokhadze, Tasman, Sokhadze, El-Baz, & Casanova, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…and adding earlier potentials (e.g., N100) and errorrelated potentials (i.e., ERN and Pe) may increase the diagnostic potential for clinical and functional evaluations of ASD. & Casanova, 2016) revealed that autism is associated with reduced error processing and impaired behavioral correction after an error is committed. Because adequate error processing is necessary for optimal behavioral performance, it is plausible that these deficits contribute to the maintenance of the preservative behaviors typical for autism.…”
Section: Perspectives Of Application Of Erp As Outcomes In Treatmentmentioning
confidence: 99%